Strategi Public Relations Dalam Memelihara Citra Pemerintah Desa Partihaman Saroha - Nurhanifah, Nurhanifah; Ananda, Brillian Heaby; Sulista, Dirga Ayu; Sulistia, Dirga Ayu; Siddiq, Muhammad; Halisa, Nurul; Rifqi, Zurrahman (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
This study discusses the public relations strategy of the Partihaman Saroha village government in maintaining a positive image. The purpose of this study is to explore and describe the public relations strategy used by local governments to maintain a positive image. This study uses four theories, namely image theory to determine the image of the government of Padang Sidimpuan District, Partihaman Saroha Village, public relations, and government public relations to determine the government's role. relationship with public relations image and strategy to determine the public relations strategy used. This type of research is descriptive and the presentation of the data is qualitative. Data were obtained from interviews with the Partihaman Saroha Village Head. From the results of the research it is known that the public relations strategy used by village officials or village heads and their members to form a positive image is media relations and Mandok Hata (said) lightly on local community complaints). The aim of the Sidimpuan Hitaimbaru sub-district government is to choose media relations as a strategy to reduce or even eliminate negative information about Partihaman Saroha village in the media, positive reporting about Padang sub-district What is the Sidimpuan Hutaimburu district government. Keywords: public relations, positive image, partihaman saroha village